First proteome of the egg perivitelline fluid of a freshwater gastropod with aerial oviposition - Sun, Jin (2012)
Pomacea canaliculata is a freshwater snail that deposits eggs on solid substrates above the water surface. Previous studies have emphasized the nutritional and protective functions of the three most abundant perivitelline fluid (PVF) protein complexes (ovorubin, PV2, and PV3) during its embryonic development, but little is known about the structure and function of other less abundant proteins. Using 2-DE, SDS-PAGE, MALDI TOF/TOF, and LC-MS/MS, we identified 59 proteins from the PVF of P. canaliculata, among which 19 are novel. KEGG analysis showed that the functions of the majority of these proteins are "unknown" (n = 34), "environmental information processing" (10), 9 of which are related to innate immunity, and "metabolism" (7). Suppressive subtractive hybridization revealed 21 PVF genes to be specific to the albumen gland, indicating this organ is the origin of many of the PVF proteins. Further, the 3 ovorubin subunits were identified with 30.2-35.0% identity among them, indicating their common origin but ancient duplications. Characterization of the PVF proteome has opened the gate for further studies aiming to understand the evolution of the novel proteins and their contribution to the switch to aerial oviposition.